Pengaruh Celebrity Endorsement, Flash Sale dan Gratis Ongkir Terhadap Keputusan Pembelian Konsumen Pada Produk Facetology di Marketplace Shopee: Studi Kasus Konsumen di Kabupaten Jember - Putri, Maulidia Rahma Eka; Murtaliningtyas, Wenny; Reskiputri, Tatit Diansari (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study analyzes celebrity endorsements, flash sales, and free shipping on consumer purchase decisions on facetology products on the Shopee marketplace (consumer case study in Jember Regency). The increasingly advanced digital era has changed people's activities, including purchasing power. In Indonesia itself, most people in all provinces in Indonesia can access the internet. Nowadays, things related to finance, business, transportation, and technology can be connected through the internet. One of the technological developments in the economic sector is the existence of e-commerce. The dominant e-commerce platform in Indonesia is Shopee. This marketplace has managed to attract the attention of consumers through various marketing strategies such as celebrity endorsements, flash sales, and free shipping services. This can also be seen in Jember regency, consumers are increasingly interested in shopping online through Shopee one of them is for beauty products such as Facetology. The sample in this study was 100 female consumers who lived in the Jember district and were over 17 years old and used the Shopee application. The sample determination technique used in this study is purposive sampling. The sampling technique used was a questionnaire distributed through Google Forms. The hypothesis test in this study uses the t-test. The results of the study show that the celebrity endorsement variable has a positive and significant effect on purchase decisions. The flash sale variable has a positive and significant effect on buyers' decisions, and finally free shipping has a positive but not significant effect on purchase decisions